Neural mechanisms of reward processing associated with depression-related personality traits. Issue 7 (July 2017) - Umemoto, Akina; Holroyd, Clay B.
Highlights: We examined individual differences in depression, reward sensitivity, and motivation. Elevated depression scores were associated with poor learning of improbable rewards. Event-related potentials revealed reduced anticipation for and processing of rewards. Abstract: Objective: Although impaired reward processing in depression has been well-documented, the exact nature of that deficit remains poorly understood. To investigate the link between depression and the neural mechanisms of reward processing, we examined individual differences in personality. Methods: We recorded the electroencephalogram from healthy college students engaged in a probabilistic reinforcement learning task. Participants also completed several personality questionnaires that assessed traits related to reward sensitivity, motivation, and depression. We examined whether behavioral measures of reward learning and event-related potential components related to outcome processing and reward anticipation—namely, the cue and feedback-related reward positivity (RewP) and the stimulus preceding negativity (SPN)—would link these personality traits to depression. Results: Participants who scored high in reward sensitivity produced a relatively larger feedback-RewP. By contrast, participants who scored high in depression learned the contingencies for infrequently rewarded cue-response combinations relatively poorly, exhibited a larger SPN, and produced a smaller feedback-RewP, especially to outcomes following cue-response combinations that were frequently rewarded. Conclusion: These results point to a primary deficit in reward valuation in individuals who score high in depression, with secondary consequences that impact reward learning and anticipation. Significance: Despite recent evidence arguing for an anticipatory deficit in depression, impaired reward valuation as a primary deficit should be further examined in clinical samples.